2018
DOI: 10.1161/strokeaha.118.022256
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Heme Oxygenase-1 Levels and Carotid Atherosclerosis

Abstract: Background and Purpose— Heme oxygenase-1 (HO-1) catalyzes the oxidation of heme to generate carbon monoxide, biliverdin, and iron. Because these products have antiatherogenic properties, HO-1 may play a protective role against atherosclerosis. However, plasma HO-1 levels in patients with carotid atherosclerosis have not been reported. Methods— We investigated plasma HO-1 levels by ELISA in 136 subjects (age, 66±9 years) undergoing carotid ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Although the precise mechanisms of secretion and the significance of the extracellular HO-1 remain to be determined, HO-1 is known to be released into the plasma by leukocytes, macrophages, smooth muscle cells, and endothelial cells that are activated or damaged by oxidative stress or inflammation [4]. Kishimoto et al hypothesized that plasma HO-1 levels may be associated with the presence and severity of carotid atherosclerosis, and they measured the plasma HO-1 levels in 136 consecutive subjects (mean age 66 ± 9 years) who underwent carotid ultrasonography for a medical check-up to evaluate atherosclerosis [25]. The study was the first to reveal that the plasma HO-1 levels were significantly higher in the subjects with carotid plaque than in those without plaque (median 0.56 versus 0.44 ng/mL, p < 0.05), and the levels were stepwisely increased depending on the severity of plaque, defined as the plaque score (Figure 1).…”
Section: Ho-1 Expression In Patients With Atherosclerotic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanisms of secretion and the significance of the extracellular HO-1 remain to be determined, HO-1 is known to be released into the plasma by leukocytes, macrophages, smooth muscle cells, and endothelial cells that are activated or damaged by oxidative stress or inflammation [4]. Kishimoto et al hypothesized that plasma HO-1 levels may be associated with the presence and severity of carotid atherosclerosis, and they measured the plasma HO-1 levels in 136 consecutive subjects (mean age 66 ± 9 years) who underwent carotid ultrasonography for a medical check-up to evaluate atherosclerosis [25]. The study was the first to reveal that the plasma HO-1 levels were significantly higher in the subjects with carotid plaque than in those without plaque (median 0.56 versus 0.44 ng/mL, p < 0.05), and the levels were stepwisely increased depending on the severity of plaque, defined as the plaque score (Figure 1).…”
Section: Ho-1 Expression In Patients With Atherosclerotic Diseasesmentioning
confidence: 99%
“…The whiskers represent the lowest and highest value in the 25th percentile minus 1.5 IQR and 75th percentile plus 1.5 IQR, respectively. (Modified from Kishimoto et al [25]).…”
Section: Figurementioning
confidence: 99%
“…The pivotal role of HO-1 is also suggested by Cheng et al, who have reported the HO-1 induction reverses plaque progression from a vulnerable to a more stable phenotype [77], which might be mediated by heme catabolism by-products. In addition, plasma HO-1 levels are higher in patients with carotid plaques compared to healthy subjects, which probably indicates a possible protective response against carotid atherosclerosis [78].…”
Section: Atherosclerosismentioning
confidence: 99%
“…The association between the presence of atherosclerosis or CAD and serum HO-1 levels has been investigated in previous studies. Kishimoto et al [16] found that patients without carotid plaques had significantly lower plasma HO-1 levels than the ones with carotid plaques (median 0.44 vs. 0.56 ng/mL, p < 0.05). Moreover, regression analysis showed that an HO-1 level >0.50 ng/mL was independently associated with the presence of carotid plaques (odds ratio: 2.33, 95% CI: 1.15–4.75, p < 0.025).…”
Section: Discussionmentioning
confidence: 99%